ETHNIC POLITICS AND DEMOCRATIC GROWTH IN NIGERIA - Otu, Eugene Chukwu (EBSU Journal of Social Sciences and Humanities, 2022)
This study interrogates “Ethnic politics and democratic growth in Nigeria”. Ethnic politics continue to pose a security threat to democratic growth in Nigeria which affects promotion of good governance and democracy in the country. Today, many ethnic regions in Nigeria continue to use ethnicity as a resource for political manipulation and entrepreneurship, resulting in dominant ethnic groups excluding minority groups within national policies that reflect the interests and activities of the national majority. The objective of this study is to interrogate ethnic politics in Nigeria, unveiling how it affects democratic growth in the country. The researcher applied Game theory in analyzing the research. The methodology used by the researcher is qualitative research method as the researcher employed secondary data.